(untitled) (Biological Sciences - PJSIR, 2021)
The recent research was directed to explore the phytochemical, antimicrobial and antioxidant activity of Hydrodictyon reticulatum L. The samples were then identified morphologically and anatomically. By using different solvents algal extracts were prepared. The phytochemical activity of algal samples were performed to determine the presence or absence of alkaloids, steroids, tannin, triterpenoids, saponin, terpenoids, quinine, coumarins, phlobatannins, phytosteroids and flavonoids. Two bacterial strains S. aureus and E. coli were used to determine the antibacterial activity of algal extracts. The greatest activity was appeared by the methanolic extract against the fungal strain S. aureus i.e. 12.5±0.088 mm, while the aqueous extract showed the maximum anti-bacterial activity that was 12.2±0.058 mm beside E. coli. These findings were relatively equivalent to the results of standard Amkasin that was normally used as antibiotic in the market. The results of antifungal movement was indicated greatest having the solvent (CH3)2CO separate i.e. 1.8±0.058 mm against A. niger. While methanol extricate indicated 2.35±0.058 mm against the strain F. solani. DPPH rummaging activity, TAA and TPC were performed to determine the action of reticulatum. In the event of DPPH the most extreme IC50 recorded was from the chloroform extricate. While in TPC methanol extricate indicated most extreme esteem 67.14±0.54 mm and in TAA ethanol showed greatest esteem i.e. 0.88±0.01 µg/L. These results demonstrated that the Hydrodictyon reticulatum had phytochemical, cancer prevention agent and antimicrobial potential and suggested for pharmaceutical use.